Conocimientos y actitudes hacia el Papanicolaou en mujeres de 25 a 64 años del Asentamiento Humano Las Vegas Iquitos 2024 - Arevalo Linares, Perla (2025)
The objective of this study was to determine the relationship between knowledge and attitude toward the Pap smear test in women aged 25 to 64 from the Las Vegas Human Settlement, Iquitos, 2024. The research followed a quantitative approach, with a non-experimental and correlational design. The sample consisted of 78 women. Interview and home visit techniques were applied using two instruments: a questionnaire to assess knowledge about the Pap smear test, with 95.0% validity and 93.5% reliability, and a Likert-type scale to measure attitude, with 96.81% validity and 94.7% reliability. The results showed that 64.1% of participants had low knowledge levels, 25.6% had medium levels, and 10.3% had optimal knowledge. Regarding attitudes toward the test, 82.1% exhibited unfavorable attitudes, while 17.9% showed favorable attitudes. Statistical analysis reported a significant relationship between the two variables, with p=0.000 and a significance level of α=0.05. It was concluded that there is a statistically significant relationship between knowledge and attitudes toward the Pap smear test in women from the Las Vegas Human Settlement, Iquitos.